Identifikasi Keanekaragaman Tumbuhan Paku (Pteridophyta) Di Kawasan Curug Panglebur Gongso Kabupaten Kendal - Nofitasari, Titin Ayuk (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Ferns are low plants that are cosmopolitan or can be found anywhere. Panglebur Gongso waterfall area is one of the areas that has the potential to become a habitat for ferns. This study aims to determine the diversity of ferns in the Panglebur Gongso waterfall area and its benefits in human life. Data collection was carried out in December 2023 using the exploration method. Data collection is done by taking photo documentation of various types of ferns in the Panglebur Gongso waterfall area, then identification includes characteristics, morphology, habitat, plant classification and benefits. The results of observations of ferns in the Panglebur Gongso waterfall area obtained 9 species of ferns consisting of 5 families including Lygodiaceae, Pteridiaceae, Thelypteridaceae, Tectariaceae and Selaginellaceae. The ferns found include Cyclosorus terminans, Christella dentata, Adiantum concinnum, Christella parasitica (L.), Lygodium circinatum, Pityrogramma calomelanos (L.), Selaginella plana, Selaginella willdenowii, and Tectaria heracleifolia. Ferns can be utilized by humans as ornamental plants, medicines, antimicrobials and antibacterials, and are beneficial for ecology in preventing soil erosion and phytoremediation.